2009
DOI: 10.1007/bf03395683
|View full text |Cite
|
Sign up to set email alerts
|

The Implicit Relational Assessment Procedure (IRAP ) and the Malleability of Ageist Attitudes

Abstract: The current study examined the malleability of implicit attitudes using the Implicit Relational Assessment Procedure (IRAP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
57
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 35 publications
0
57
0
2
Order By: Relevance
“…As predicted, response latencies were faster for consistent than for inconsistent trials (e.g., participants responded more quickly to Pleasant-Love-Similar than to Pleasant-Love-Opposite). These results have since been replicated across a small number of other studies (e.g., Barnes-Holmes, Murphy, BarnesHolmes, & Stewart, 2010;Barnes-Holmes, Waldron, Barnes-Holmes, & Stewart, 2009;Cullen, Barnes-Holmes, Barnes-Holmes, & Stewart, 2009;Dawson, Barnes-Holmes, Gresswell, Hart & Gore, 2009;McKenna et al, 2007;Power, Barnes-Holmes, Barnes-Holmes, & Stewart, 2009;Roddy, Stewart, & BarnesHolmes, in press;Vahey, Barnes-Holmes, Barnes-Holmes, & Stewart, 2009). Nevertheless, research on the IRAP as an implicit measure is very limited, and further empirical study is required before its reliability and validity can be determined.…”
mentioning
confidence: 58%
“…As predicted, response latencies were faster for consistent than for inconsistent trials (e.g., participants responded more quickly to Pleasant-Love-Similar than to Pleasant-Love-Opposite). These results have since been replicated across a small number of other studies (e.g., Barnes-Holmes, Murphy, BarnesHolmes, & Stewart, 2010;Barnes-Holmes, Waldron, Barnes-Holmes, & Stewart, 2009;Cullen, Barnes-Holmes, Barnes-Holmes, & Stewart, 2009;Dawson, Barnes-Holmes, Gresswell, Hart & Gore, 2009;McKenna et al, 2007;Power, Barnes-Holmes, Barnes-Holmes, & Stewart, 2009;Roddy, Stewart, & BarnesHolmes, in press;Vahey, Barnes-Holmes, Barnes-Holmes, & Stewart, 2009). Nevertheless, research on the IRAP as an implicit measure is very limited, and further empirical study is required before its reliability and validity can be determined.…”
mentioning
confidence: 58%
“…Consistent with published IRAP research (e.g. Cullen et al 2009 ), the response latency data for each participant were transformed into a D-score, which represents the difference between consistent and inconsistent responding. In order to compare responding on the four main trial-types, the D-scores were then transformed into DIRAP-(trial-type) scores, which were then collapsed according to trial-type to generate a D-score for each trial-type (PUPIL vs. EBD PUPIL).…”
Section: Irap Resultsmentioning
confidence: 99%
“…In simple terms, the methodology predicts that on average, participants will respond more quickly to pairings that reflect well-established beliefs than to those that do not, and the IRAP assesses the response latency differences between these. Numerous published studies attest to the utility of this measure for the study of socially sensitive attitudes, including teachers' attitudes to pupils, preference for social groups (Power et al 2009), attitudes to body image (Roddy, Stewart, and Barnes-Holmes 2010) and ageism (Cullen et al 2009). The research by Scanlon et al (submitted) employed an IRAP that juxtaposed TEACHER and EBD PUPIL, in conjunction with positive and negative terms.…”
mentioning
confidence: 99%
“…Evidence for discriminant validity may further be inferred from studies that have shown differential effects of an intervention on IRAP versus explicit measures of the same target (Cullen et al, 2009;Hooper et al, 2010;Scheel, Fischer, McMahon, Mena, & Wolf, 2011 Two further articles report significant correlations between IRAP and explicit indices of the same targets Timko, England, Herbert, & Forman, 2010). However, these studies examined many relationships (e.g., 100 correlations across two studies in Timko et al, 2010) without adjusting for multiple testing and findings could partially reflect an inflated Type I error-rate.…”
Section: Experimental Experimental Validity Ismentioning
confidence: 99%